Clinical characteristics of posterior segment penetrating eye injuries treated in tertiary referral hospital in Serbia - Kovačević, Igor; Radosavljević, Aleksandra; Karadžić, Jelena; Stefanović, Ivan; Vukadinović, Jovana (Vojnosanitetski pregled, 2021)
Background/Aim. Ocular trauma is a significant cause of visual impairment worldwide. The aim of the study was to analyze clinical characteristics of patients with penetrating eye injuries with retained intraocular foreign body (IOFB) in posterior segment of the eye. Methods. The retrospective study enrolled medical records of consecutive patients hospitalized in a five year period (2012–2016) in a tertiary referral center in Serbia. Surgical repair included pars plana vitrectomy and IOFB removal. Postoperative results were evaluated using the best corrected visual acuity (BCVA). Results. Out of 130 patients who suffered penetrating eye injury with retained IOFB, 72 had IOFB in posterior segment of the eye (43 in retina, 25 in vitreous, 3 in ciliary body, 1 on the optic nerve). Patients were predominantly young adults (aged 44.3 ± 14.9 years, 97.2% men). Average BCVA at admission was poor (0.27 ± 0.38, measured by Snellen chart), and 52.8% of patients had BCVA of counting fingers at 1 meter or less. The majority of patients had corneal wound (70.8%), medium sized IOFB (48.6%), iris injury (61.1%) and traumatic cataract (69.4%). Complications included retinal detachment (16.7%) and endophthalmitis (15.3%). Two patients had the eye enucleated due to severe endophthalmitis, which could not be otherwise controlled. Significant risk factors for postoperative outcome were: initial BCVA (p < 0.001), ocular hypotony (p = 0.013), medium size of IOFB (p = 0.037), presence of traumatic cataract (p = 0.036), retinal detachment (p = 0.032) and endophthalmitis (p = 0.045). Conclusion. Treatment of posterior segment penetrating eye injuries remains a challenge due to high frequency of low initial visual acuity, retinal detachment and endophthalmitis, all of which are risk factors for poor visual outcome. Patients with better initial BCVA, normal intraocular pressure and small IOFB have better postoperative results.